Sustained Release of MiR-217 Inhibitor by Nanoparticles Facilitates MSC-Mediated Attenuation of Neointimal Hyperplasia After Vascular Injury - Yu, Hong; Hua, Yutao; He, Yecheng; Wang, Yin; Hu, Xingjian; Chen, Si; Liu, Junwei; Yang, Junjie; Li, Huadong (Frontiers in Cardiovascular Medicine, 2021)
Mesenchymal stem cells (MSCs) have been proven capable of differentiating into endothelial cells (ECs) and increasing vascular density in mouse ischemia models. However, the therapeutic potential of MSCs in neointimal hyperplasia after vascular injury is still not fully understood. In this study, we proposed that sustained release of miR-217 inhibitor encapsulated by nanoparticles in MSCs can enhance the therapeutic effects of MSCs on alleviating neointimal hyperplasia in a standard mouse wire injury model. We intravenously administered MSCs to mice with injured arteries and examined neointimal proliferation, endothelial differentiation and senescence. We demonstrated that MSCs localized to the luminal surface of the injured artery within 24 h after injection and subsequently differentiated into endothelial cells, inhibited neointimal proliferation and migration of vascular smooth muscle cells. Transfection of MSCs with poly lactic-co-glycolic acid nanoparticles (PLGA-NP) encapsulating an miR-217 agomir abolished endothelial differentiation as well as the therapeutic effect of MSCs. On the contrary, silencing of endogenous miR-217 improved the therapeutic efficacy of MSCs. Our study provides a new strategy of augmenting the therapeutic potency of MSCs in treatment of vascular injury.